On Visitations (KULT_online, 2022)
In his monograph, Transmitted Wounds. Media and the Mediation of Trauma, Amit Pinchevski develops the thesis that modern mass media can transmit and obliterate trauma and pleads for using ‘trauma’ as a moral category. His work interlinks memory, communication and technology studies and touches upon clinical and psychological contributions to notions of ‘trauma.’ Combining numerous views on the echoes of violence and technology, Pinchevski contributes in an inventive and inspirational way to those disciplines.